Mesoporous titanium dioxide / anodic aluminum oxide / mesoporous carbon-doped iron oxide heterogeneous nanochannel as well as preparation method and application thereof

By growing mesoporous carbon doped with iron oxide and mesoporous titanium dioxide on the surface of anodic aluminum oxide, a regular and ordered nanochannel structure was constructed, which solved the problem of unstable performance of nanochannels in the prior art and achieved improved ion selectivity and photoresponse, making it suitable for analytical sensing.

CN121298855APending Publication Date: 2026-01-09FUDAN UNIVERSITY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202511351827.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-22
Publication Date
2026-01-09

AI Technical Summary

Technical Problem

The existing photoresponsive nanochannel structures are disordered, resulting in unstable performance of the assembled nanofluidic devices. Furthermore, the single composition makes post-modification difficult, limiting their application in the field of analytical sensing.

Method used

A mesoporous carbon-doped iron oxide and mesoporous titanium dioxide were grown on the surface of anodic aluminum oxide using an evaporation-induced self-assembly strategy. The mesoporous titanium dioxide/anodic aluminum oxide/mesoporous carbon-doped iron oxide heterogeneous nanochannels were constructed through two interfacial superassemblies, forming a regular and ordered pore structure and introducing abundant negatively charged sites such as carboxyl and hydroxyl groups on the surface.

Benefits of technology

A nanochannel with abundant and highly selective ion diffusion pathways was realized, which can respond rapidly to photoexcitation current under illumination and intelligently regulate ion transport, thereby improving the performance stability and functional diversity of the nanochannel.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121298855A_ABST
    Figure CN121298855A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of analytical sensing, and particularly relates to a mesoporous titanium dioxide / anodic aluminum oxide / mesoporous carbon-doped iron oxide heterogeneous nanochannel as well as a preparation method and application of the mesoporous titanium dioxide / anodic aluminum oxide / mesoporous carbon-doped iron oxide heterogeneous nanochannel. The preparation method comprises the following steps: preparing a mesoporous carbon-doped iron oxide precursor solution from a carbon source, an iron source and F127, preparing a mesoporous titanium dioxide precursor solution from a titanium source and P123 as template agents, and preparing the mesoporous carbon-doped iron oxide / titanium dioxide composite material by using a hydrogen bond formed by the precursor solution and a hydroxyl group on the surface of AAO and by using the AAO as a substrate by virtue of a spin-coating method. And two layers of mesoporous films are tightly grown on the AAO substrate through a multi-element assembly and evaporation-induced self-assembly construction strategy. The prepared sandwich structure heterogeneous nano-channel is regular in aperture, a mesoporous skeleton has abundant surface groups which are easy to post-modify, and photosensitive nano-particles have good photoresponse and are expected to provide good light-controlled ion transport capacity, thereby providing a reliable technical support for development of intelligent nano-channels and having wide application prospects. The method has potential application value in the fields of energy conversion and biosensing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of nanochannels, specifically relating to a mesoporous titanium dioxide / anodic aluminum oxide / mesoporous carbon-doped iron oxide heterostructure nanochannel, its preparation method, and its application. Background Technology

[0002] Ion channels in living organisms are composed of membrane proteins and polypeptides embedded in cell membranes. They regulate transmembrane ion transport in response to external stimuli, playing a crucial role in life activities such as signal transduction. However, most ion channels in living organisms are constructed based on lipid membranes, making them very fragile and unstable, limiting their practical applications. In recent years, inspired by ion channels in living organisms, researchers have developed various artificial nanochannels with different functions. Artificial nanochannels are similar to biological ion channels in structure and function, but possess greater mechanical stability and tunable surface chemistry, thus showing greater promise for practical applications. Among the many artificial nanochannels, photo-controlled nanochannels offer advantages such as non-invasive remote control, high temporal resolution, and the ability to flexibly change the wavelength and intensity of incident light, enabling precise control of ion transport within the nanochannel. Currently, researchers have developed various strategies for constructing photoresponsive nanochannels, such as filtration, electrochemical oxidation, and interfacial polymerization.

[0003] CN117643800A discloses a permeability-tunable UV-responsive nanochannel membrane, composed of a membrane substrate and a UV-responsive functional material grafted onto the surface of the membrane substrate. The membrane substrate has uniformly distributed nanochannels with uniform pore size. The UV-responsive material consists of a coumarin core, a carbon framework, and coupling groups R. Under UV irradiation at different wavelengths and irradiation doses, the UV-responsive functional material grafted onto the membrane substrate surface undergoes photopolymerization to form dimers or photolysis of dimers, causing changes in the degree of polymerization of the UV-responsive material. This, in turn, alters the opening degree of the nanochannels in the UV-responsive nanochannel membrane, achieving controllable adjustment of the permeability of the UV-responsive nanochannel membrane. CN117123067A discloses a photoresponsive nanochannel membrane, its preparation method, and its applications. The preparation method is as follows: dissolve the thioyl fluoride photoresponsive molecule in an acetonitrile solution containing a catalyst to obtain a grafting solution; immerse the covalent organic framework composite membrane in the grafting solution and allow it to react statically to obtain a photoresponsive nanochannel membrane.

[0004] The disordered nanochannel structures prepared by existing technologies lead to unstable performance of assembled nanofluidic devices, affecting the controllable regulation of ion transport processes. Furthermore, the constructed nanochannels have a single composition and limited surface functional groups, making post-modification difficult and restricting their application in analytical sensing. Therefore, developing multi-component photocontrolled nanochannels with highly ordered nanochannel structures and excellent photoresponse properties is particularly important. Summary of the Invention

[0005] This invention aims to address the bottlenecks currently faced by photoresponsive smart nanochannels, and provides a mesoporous titanium dioxide / anodic aluminum oxide / mesoporous carbon-doped iron oxide (NMTI / AAO / MC-γ-Fe2O3) heterostructure nanochannel based on evaporation-induced self-assembly and multi-element assembly strategies, as well as its preparation method.

[0006] This application provides a mesoporous titanium dioxide / anodic aluminum oxide / mesoporous carbon-doped iron oxide heterostructure nanochannel, which is prepared by evaporation-induced self-assembly on an anodic aluminum oxide (AAO) surface to grow mesoporous carbon-doped iron oxide and mesoporous titanium dioxide.

[0007] This application provides a method for preparing a mesoporous titanium dioxide / anodic aluminum oxide / mesoporous carbon-doped iron oxide heterogeneous nanochannel. Utilizing the hydrogen bonds formed between the precursor solution and the anodic aluminum oxide (AAO) surface, a mesoporous carbon-doped iron oxide film and a mesoporous titanium dioxide film are grown on the AAO surface through a two-stage interfacial superassembly and evaporation-induced self-assembly construction strategy. The AAO film used in this application has a thickness of 60 μm, an average pore size of 80 nm-100 nm, and a diameter of 15 mm.

[0008] Furthermore, mesoporous carbon dioxide and mesoporous carbon-doped iron oxide are located on opposite sides of the surface of the anodic aluminum oxide;

[0009] Furthermore, the thickness of the mesoporous carbon-doped iron oxide grown on the AAO surface is 50-70 nm, and the thickness of the mesoporous titanium dioxide is 140-180 nm.

[0010] The preparation method includes the following steps:

[0011] (1) Preparation of mesoporous carbon doped iron oxide precursor solution: The template agent, carbon source, iron source and solvent are mixed to obtain mesoporous carbon doped iron oxide precursor solution;

[0012] (2) Preparation of mesoporous titanium dioxide precursor solution: The template agent, titanium source and solvent are mixed to obtain mesoporous titanium dioxide precursor solution;

[0013] (3) Preparation of mesoporous titanium dioxide / anodic aluminum oxide / mesoporous carbon doped iron oxide heterogeneous nanochannels: The mesoporous carbon doped iron oxide precursor solution and the mesoporous titanium dioxide precursor solution are sequentially spin-coated onto the surface of double-sided pore-blocking anodic aluminum oxide, and then assembled by evaporation-induced assembly to obtain mesoporous titanium dioxide / anodic aluminum oxide / mesoporous carbon doped iron oxide heterogeneous nanochannels.

[0014] Further, in step (1), the template agent is added to the solvent and sonicated until clear, then a carbon source is added and stirred for 10-20 min, then an iron source is added and stirred for 30-40 min;

[0015] Further, in step (2), concentrated hydrochloric acid is slowly added to the titanium source and stirred at room temperature for 10-15 minutes. The template agent is dissolved in the solvent and then added to the mixed solution of concentrated hydrochloric acid and titanium source. Stirring continues for 15-20 minutes.

[0016] Further, in step (3), the mesoporous carbon doped iron oxide precursor solution and the mesoporous titanium dioxide precursor solution are spin-coated sequentially onto the surface of the double-sided plugged anodic aluminum oxide, evaporation-induced assembly is performed, and calcination is carried out to obtain a mesoporous titanium dioxide / anodic aluminum oxide / mesoporous carbon doped iron oxide heterogeneous nanochannel.

[0017] Furthermore, after evaporation-induced assembly, the mesoporous carbon-doped iron oxide precursor solution was spin-coated and assembled at room temperature and 100-110℃ for 24-36 hours each; after spin-coating the mesoporous titanium dioxide precursor solution, the assembly was carried out at -25 to -20℃ for 24-36 hours; finally, the mixture was calcined at 400-450℃ for 4-5 hours under a nitrogen atmosphere.

[0018] Evaporation-induced self-assembly is key to generating regular and ordered channels. At room temperature, low temperature and 100-110℃, the solvent evaporates, and the metal source and template agent co-assemble to form an ordered mesoscopic structure.

[0019] Furthermore, the solvent is selected from ethanol or tetrahydrofuran to provide a stable environment for the assembly of the precursor solution.

[0020] Further, in step (1), a mesoporous carbon-doped iron oxide precursor solution is prepared, with F127 as the template agent, phenolic resin prepolymer resol as the carbon source, and the iron source selected from at least one of acetylacetone iron or ferric nitrate.

[0021] F127 is a polyepoxy triblock copolymer, specifically model Pluronic F-127, also known as Polozham in Chinese, and its standard Chinese name is polyepoxy triblock copolymer F127.

[0022] Further, in step (1), a mesoporous carbon-doped iron oxide precursor solution is prepared. The ratio of template agent: carbon source: iron source: solvent is 0.125-0.25:1.25-2.5:1.89-7.56:1.25-2.5 by mass, and the molar concentration of the iron source is 0.03-0.05 mmol / L / g.

[0023] Further, in step (2), a mesoporous titanium dioxide precursor solution is prepared, with P123 as the template agent and at least one titanium source selected from tetraisopropyl titanate or titanium tetrachloride.

[0024] P123 is a polyepoxy triblock copolymer, specifically model Pluronic P-123, and its Chinese standard name is polyepoxy triblock copolymer P123.

[0025] Further, in step (2), a mesoporous titanium dioxide precursor solution is prepared, with the ratio of titanium source: template agent: solvent being 1.05-1.2:0.20-0.23:3-3.4 by mass.

[0026] Furthermore, a 10-12.5 wt.% acetone solution of polymethyl methacrylate (PMMA) was used as the plugging agent for double-sided plugging;

[0027] Stir the plugging agent at 35-40℃ for 12-16 hours; take 200-400μL of the plugging agent and spin-coat it to evenly cover the surface of the AAO membrane; transfer the spin-coated AAO membrane to a well-ventilated environment and allow it to dry naturally at room temperature; then place it in an oven preheated to 200-220℃ and continue drying for 5-8 hours to ensure that the PMMA fully penetrates and cures in the AAO pores;

[0028] Furthermore, the spin coating speed is 3000-3500 rpm and the spin coating time is 30-45 s.

[0029] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0030] The mesoporous titanium dioxide / anodic aluminum oxide / mesoporous carbon-doped iron oxide heterostructure nanochannels prepared in this invention provide abundant ion diffusion pathways through the well-ordered mesoporous channels on the surface of the mesoporous layer, and excellent ion selectivity due to the abundant negatively charged sites such as carboxyl and hydroxyl groups on the surface. The content and size of the γ-Fe₂O₃ particles embedded in the mesoporous carbon can be effectively controlled. Furthermore, as a semiconductor material, due to its photothermal properties, it generates a photoexcitation current under illumination, exhibiting a rapid and sensitive response to light stimulation and demonstrating excellent photothermal effects. Ion transport can be intelligently controlled under illumination. Attached Figure Description

[0031] Figure 1This is a schematic diagram illustrating the principle of preparing mesoporous titanium dioxide / anodic aluminum oxide / mesoporous carbon-doped iron oxide (NMTI / AAO / MC-γ-Fe2O3) heterogeneous nanochannels in this application;

[0032] Figure 2 This is a scanning electron microscope (SEM) image of the surface of the NMTI side of the mesoporous titanium dioxide / anodic aluminum oxide / mesoporous carbon-doped iron oxide heterostructure nanochannel prepared in Example 1;

[0033] Figure 3 This is a cross-sectional scanning electron microscope (SEM) image of the MC-γ-Fe2O3 side of the mesoporous titanium dioxide / anodic aluminum oxide / mesoporous carbon-doped iron oxide heterostructure nanochannel prepared in Example 1.

[0034] Figure 4 This is a transmission electron microscope (TEM) image of the mesoporous titanium dioxide thin film prepared in Example 1;

[0035] Figure 5 This is a transmission electron microscope (TEM) image of the mesoporous carbon-doped iron oxide thin film prepared in Example 1;

[0036] Figure 6 The nitrogen adsorption-desorption curves of the mesoporous titanium dioxide material prepared in Example 1 are shown.

[0037] Figure 7 This is a pore size distribution diagram of the mesoporous titanium dioxide material prepared in Example 1;

[0038] Figure 8 The nitrogen adsorption-desorption curves of the mesoporous carbon-doped iron oxide material prepared in Example 1 are shown.

[0039] Figure 9 This is a pore size distribution diagram of the mesoporous carbon-doped iron oxide material prepared in Example 1. Detailed Implementation

[0040] The present invention will now be described more fully with reference to specific embodiments.

[0041] Example 1

[0042] The preparation steps of the mesoporous titanium dioxide / anodic aluminum oxide / mesoporous carbon-doped iron oxide heterostructure nanochannel are as follows:

[0043] 1) Preparation of mesoporous carbon doped iron oxide precursor solution: 0.25g of F127 was added to 2.5g of ethanol solution and sonicated until clear. 1.25g of phenolic resin prepolymer resol was added and stirred for 10-20min. 7.56g of 0.03mmol / L / g acetylacetone iron ethanol solution was added and stirred for 30min.

[0044] 2) Preparation of heterogeneous nanochannel mesoporous carbon doped with iron oxide side: The prepared precursor solution was spin-coated onto the surface of AAO and assembled at room temperature and 100℃ for 24 h each.

[0045] 3) Preparation of mesoporous titanium dioxide precursor solution: Add 0.2g of P123 to 3g of ethanol solution and sonicate until clear. Add 1.05g of titanium tetrachloride and stir for 10-20min.

[0046] 4) Preparation of heterogeneous nanochannel mesoporous carbon-doped iron oxide side: The prepared precursor solution was spin-coated onto the AAO surface and assembled at -20℃ for 24 h. The template agent was removed by calcination at 400℃ under a nitrogen atmosphere for 4 h.

[0047] Figure 1 This is a schematic diagram illustrating the technical solution of this application. Figures 2-9 All results are experimental test results of the mesoporous titanium dioxide / anodic aluminum oxide / mesoporous carbon-doped iron oxide heterostructure nanochannels prepared in Example 1.

[0048] Figure 2 The image shows a surface scanning electron microscope (SEM) image of the NMTI side of the mesoporous titanium dioxide / anodic aluminum oxide / mesoporous carbon-doped iron oxide (NMTI / AAO / MC-γ-Fe2O3) heterogeneous nanochannel. The image shows that the mesoporous titanium dioxide nanopillar array is partially interconnected, exhibiting a unique mesoscopic structure.

[0049] Figure 3 The image shows a scanning electron microscope (SEM) image of the MC-γ-Fe2O3 side of the mesoporous titanium dioxide / anodic aluminum oxide / mesoporous carbon doped iron oxide (NMTI / AAO / MC-γ-Fe2O3) heterogeneous nanochannel prepared in this invention. The image shows that the mesoporous carbon has uniform pore size, high orderliness, and a smooth surface.

[0050] Figure 4 This is a transmission electron microscope (TEM) image of the mesoporous titanium dioxide thin film prepared in this invention.

[0051] Figure 5 These are transmission electron microscope (TEM) images of the mesoporous carbon-doped iron oxide thin film prepared by this invention. As can be seen from the two images, the mesoporous channels on both sides of AAO are regular and orderly, providing abundant transport paths for ion transport. The γ-Fe2O3 particles are partially embedded on the surface of the mesoporous carbon, uniformly distributed, and without obvious agglomeration, which is expected to provide good photoresponse properties.

[0052] The titanium dioxide mesoporous film and the carbon-doped iron oxide mesoporous film on the AAO template were scraped off with a scraper for nitrogen adsorption-desorption testing. Figure 6 This is the nitrogen adsorption-desorption curve of the mesoporous titanium dioxide material prepared by this invention. Figure 7This is a pore size distribution diagram of the mesoporous titanium dioxide material prepared by the present invention. Figure 8 This is the nitrogen adsorption-desorption curve of the mesoporous carbon-doped iron oxide material prepared by this invention. Figure 9 This is a pore size distribution diagram of the mesoporous carbon-doped iron oxide materials prepared by this invention. The nitrogen adsorption-desorption isotherms of both materials belong to typical Type IV curves, confirming that both synthesized thin film materials possess a highly ordered mesoporous structure. The pore size distribution curves of both materials exhibit a single-peak mesoporous distribution, centered at 4.72 nm and 4.30 nm, respectively.

[0053] Example 2

[0054] The preparation steps of the mesoporous titanium dioxide / anodic aluminum oxide / mesoporous carbon-doped iron oxide heterostructure nanochannel are as follows:

[0055] 1) Preparation of mesoporous carbon doped iron oxide precursor solution: 0.125 g of F127 was added to 1.25 g of tetrahydrofuran solution and sonicated until clear. 2.5 g of phenolic resin prepolymer resol was added and stirred for 10-20 min. 1.89 g of 0.05 mmol / L / g ferric nitrate ethanol solution was added and stirred for 30 min.

[0056] 2) Preparation of heterogeneous nanochannel mesoporous carbon doped with iron oxide side: The prepared mesoporous carbon doped with iron oxide precursor solution was spin-coated onto the AAO surface and assembled at room temperature and 110℃ for 36 h each.

[0057] 3) Preparation of mesoporous titanium dioxide precursor solution: Add 0.23g of P123 to 3.4g of tetrahydrofuran solution and sonicate until clear. Add 1.25g of tetraisopropyl titanate and stir for 10-20min.

[0058] 4) Preparation of heterogeneous nanochannel mesoporous carbon-doped iron oxide side: The prepared mesoporous titanium dioxide precursor solution was spin-coated onto the AAO surface and assembled at -25℃ for 36 h. The template agent was removed by calcination at 450℃ under a nitrogen atmosphere for 5 h.

Claims

1. A mesoporous titanium dioxide / anodic aluminum oxide / mesoporous carbon-doped iron oxide heterogeneous nanochannel, characterized in that, Mesoporous carbon doped with iron oxide and mesoporous titanium dioxide was prepared by evaporation-induced self-assembly on the surface of anodic aluminum oxide.

2. The mesoporous titanium dioxide / anodic aluminum oxide / mesoporous carbon-doped iron oxide heterogeneous nanochannel according to claim 1, characterized in that, The mesoporous carbon dioxide and mesoporous carbon doped with iron oxide are located on opposite sides of the surface of the anodic aluminum oxide; The thickness of the mesoporous carbon-doped iron oxide is 50-70 nm, and the thickness of the mesoporous titanium dioxide is 140-180 nm.

3. A method for preparing a mesoporous titanium dioxide / anodic aluminum oxide / mesoporous carbon-doped iron oxide heterostructure nanochannel as described in claim 1 or 2, characterized in that, Including the following steps: Preparation of mesoporous carbon doped iron oxide precursor solution: The template agent, carbon source, iron source and solvent are mixed to obtain the mesoporous carbon doped iron oxide precursor solution; Preparation of mesoporous titanium dioxide precursor solution: The template agent, titanium source and solvent are mixed to obtain mesoporous titanium dioxide precursor solution; Preparation of mesoporous titanium dioxide / anodic aluminum oxide / mesoporous carbon-doped iron oxide heterostructure nanochannels: First, the mesoporous carbon-doped iron oxide precursor solution was spin-coated onto the pore-blocking surface of anodic aluminum oxide, and evaporation-induced assembly was performed; then, the mesoporous titanium dioxide precursor solution was spin-coated onto the pore-blocking surface of anodic aluminum oxide, and evaporation-induced assembly was performed; calcination was then performed to obtain the mesoporous titanium dioxide / anodic aluminum oxide / mesoporous carbon-doped iron oxide heterostructure nanochannels.

4. The preparation method according to claim 3, characterized in that, The evaporation-induced assembly includes the following steps: After spin-coating a mesoporous carbon-doped iron oxide precursor solution, the assembly was first performed at room temperature, and then at 100–110 °C; after spin-coating a mesoporous titanium dioxide precursor solution, the assembly was performed at -25–-20 °C.

5. The preparation method according to claim 3, characterized in that, The calcination is carried out under a nitrogen atmosphere at a temperature of 400–450°C.

6. The preparation method according to claim 3, characterized in that, The solvent is selected from ethanol or tetrahydrofuran.

7. The preparation method according to claim 3, characterized in that, In the step of preparing the mesoporous carbon-doped iron oxide precursor solution, the template agent is a polyethylene oxide triblock copolymer F127, the carbon source is a phenolic resin prepolymer resol, and the iron source is selected from at least one of acetylacetone iron or ferric nitrate.

8. The preparation method according to claim 3, characterized in that, In the step of preparing the mesoporous carbon-doped iron oxide precursor solution, the ratio of template agent: carbon source: iron source: solvent is 0.125-0.25:1.25-2.5:1.89-7.56:1.25-2.5 by mass, and the molar concentration of the iron source is 0.03-0.05 mmol / L / g.

9. The preparation method according to claim 3, characterized in that, In the step of preparing the mesoporous titanium dioxide precursor solution, the template agent is a polyethylene oxide triblock copolymer P123, and the titanium source is selected from at least one of tetraisopropyl titanate or titanium tetrachloride.

10. The preparation method according to claim 3, characterized in that, In the step of preparing the mesoporous titanium dioxide precursor solution, the ratio of titanium source: template agent: solvent is 1.05-1.2:0.20-0.23:3-3.4 by mass.

11. The preparation method according to claim 3, characterized in that, The double-sided plugging is made of 10-12.5 wt% polymethyl methacrylate in acetone solution.

12. The application of the mesoporous titanium dioxide / anodic aluminum oxide / mesoporous carbon-doped iron oxide heterostructure nanochannel as described in claim 1 in intelligent regulation of ion transport.

Citation Information

Patent Citations

  • Photoresponse nano-channel film as well as preparation method and application thereof

    CN117123067A